I Can't Get No Satisfaction: The Power of Perceived Differences in Employee Retention and Turnover - Deniz Gevrek; Marilyn Spencer; David Hudgins; Valrie Chambers (Institute of Labor Economics (IZA), 2017)
This study explores the role of salary raises and the perception of employees of these salary raises on employees' intended retention and turnover. By using a unique survey data set from an American university, this study investigates a novel hypothesis that faculty perceptions of salary raises, relative to their perceptions of other faculty members' assessments of the raises, influences their labor supply. Using both Ordered Probit and OLS modelling frameworks, we focus on the impact of salary raises and the relative perception of these raises on intended labor supply behavior. We explore a hypothesis that a mismatch between one's ranking of the salary raise and the perception of others' rankings causes dissatisfaction. Our results provide evidence that salary raises themselves are effective monetary tools to reduce turnover; however, our results also suggest that relative deprivation as a comparison of one's own perceptions of a salary raise with others affects employee retention. We find that employees who have less favorable perceptions of salary adjustments, compared to what they believe their colleagues think, are more likely to seek another employer, holding their own perception of raises constant. Conversely, more favorable views of salary raises, compared to how faculty members think other's perceived the salary raises, does not have a statistically significant impact on retention. Our results indicate that monetary rewards in the form of salary raises do impact employee retention; however, perception of fairness of these salary raises is also as important as the actual raises. Given the high cost of job turnover, these findings suggest that employers would benefit from devoting resources toward ensuring that salary- and raise-determining procedures are generally perceived by the vast majority of employees as being fair. This is the first study that explores the employee satisfaction with salary raises relative to perceptions of other employees' satisfaction with salary raises, and intended labor supply in an American university.
Keywords: I23; J22; J28; M52; 330; employee turnover; labor supply; higher education; job satisfaction; ordered probit model; relative perception; relative deprivation